Interplay between Depressive-Like Behavior and the Immune System in an Animal Model of Prenatal Dexamethasone Administration - Roque, Susana; Oliveira, Tiago G.; Nobrega, Claudia; Barreira-Silva, Palmira; Nunes-Alves, Cláudio; Sousa, Nuno; Palha, Joana A.; Correia-Neves, Margarida (Frontiers in Behavioral Neuroscience, 2011)
Glucocorticoids, namely dexamethasone, are prescribed during late gestation in pregnancies at risk of originating premature newborns, to promote fetal lung maturation. However, adverse early life events have been reported to induce long-lasting changes in the immune and central nervous systems. The accumulating evidence on bidirectional interactions between both systems in psychiatric disorders like depression, prompted us to further investigate the long term impact of prenatal dexamethasone in depressive-like behavior, the immune system and in the ability to mount an immune response to acute infection. The adult male offspring of pregnant dams treated with dexamethasone, present depressive-like behavior concomitant with a decrease in CD8+ T lymphocytes and an increase in B and CD4+ regulatory T cells. This is accompanied by lower levels of serum interleukine-6 (IL-6) and IL-10. Despite of these differences, when spleen cells are stimulated, in vitro, with lipopolysaccharide, those from adult rats prenatally treated with dexamethasone display a stronger pro-inflammatory cytokine response. However, this immune system profile does not hamper the ability of rats prenatally treated with dexamethasone to respond to acute infection by Listeria monocytogenes. Of notice, L. monocytogenes infection triggers depressive-like behavior in control animals but does not worsen that already present in dexamethasone-treated animals. In summary, prenatal administration of dexamethasone has long lasting effects on the immune system and on behavior, which is not further aggravated by acute infection with L. monocytogenes.